Penerapan Model Quantum Learning dalam Meningkatkan Hasil Belajar pada Pembelajaran IPA - Akhmad Sarojo; Lailatun Nikmah H; Alwi Muhrudin; Umi Muslikhah; Nur Ahmad Sularso; Sugiyatmi Sugiyatmi (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Learning outcomes are the main indicator in assessing the success of the learning process. These outcomes not only reflect students' academic achievements but also reflect the effectiveness of teaching methods, the role of teachers, and the overall learning environment. One learning model for fostering cooperation is the Quantum Learning model. This research method uses a qualitative approach. The informants in this study are science teachers. Data collection techniques include interviews, observations, and documentation. The research findings are as follows: 1) The steps of the Quantum Learning model include nurture, experience, name, demonstrate, and repeat. 2) The advantages of the Quantum Learning model are a positive attitude, increased motivation, and lifelong learning skills; 3) The disadvantages of the Quantum Learning model are that it requires and demands more specialized teacher skills and expertise, as well as a well-planned and well-prepared learning process. The conclusion of this study is that the Quantum Learning model can be applied in the learning process as an effort to improve learning outcomes during the learning process and is effective in enhancing science learni